THU0314 Bone status of children born from mothers with autoimmune diseases treated during pregnancy with low molecular weight heparin and/or prednisone. (23rd January 2014) - Pagnini, I.; Simonini, G.; Cavalli, L.; la Marca, G.; Sollai, S.; Iuliano, A.; Brandi, M.L.; Bellisai, F.; Galeazzi, M.; Cantarini, L.; Cimaz, R.
Abstract : Background: Women with autoimmune diseases can often lead a normal life and give birth to healthy children; however disease activity and drugs administered during pregnancy can potentially have an effect on their offspring. Bone health is influenced by many factors, some of them starting at birth or even during prenatal life. Heparin is known to cause bone loss, and data on its transplacental passage are scanty. Objectives: To evaluate bone status with phalangeal ultrasound and parameters of bone metabolism in children born from a cohort of mothers with autoimmune diseases and treated with agents known to reduce bone mass. Methods: We have enrolled 40 children born from mothers with autoimmune diseases who were treated during pregnancy with low molecular weight heparin (LMVH) and/or prednisone. History and physical examination (including body mass index), laboratory tests including bone alkaline phosphatase, osteocalcin, ICTP telopeptide, vitamin D levels, and phalangeal ultrasonography (DBM Sonic Italy), were performed in all cases. Demographic, clinical, and laboratory data were entered into a customized database, and results were analyzed with SPSS software. In some children whose mothers were treated with LMWH, we retrieved dried blood spots taken after 48 hours of life for newborn screening purposes and we analyzed the possible presence of heparin with a new liquid chromatography tandem mass spectrometry method. Results: We enrolled 26 girls and 14 boys (mean age 5y10mo, range 9mo-11y), born from 30 mothers with SLE or connective tissue diseases. These women had been continuously treated during pregnancy with daily LMWH (n=10), prednisone (n=15), or both (n=15). Fetal distress was recorded in 4 cases, prematurity in 14, neonatal complications in 7. Median birth weight was 2935 g, range 520-3790. Growth and development were within normal limits for age in all cases, clinical examination did not show major abnormalities, and laboratory tests were normal for age. Despite previous supplementation in 37/40, vitamin D serum levels were decreased (<30 ng/ml) in 25 children. Bone ultrasound revealed low values (<3 centile, corrected for age and sex) in 10 patients. No fractures were recorded. In univariate analysis, low ultrasound values (≤3 centile) showed a significant correlation with age at examination (rs : 0.41, p<0.006) and osteocalcin values (rs : -0.32, p<0.04). No significant correlations were detected with the other entered variables, including LMWH and steroid use exposure. In a multi-stepwise regression analysis weighted for BMI values, young age at examination resulted the single predictor of low ultrasound values (multiple R=0.44, multiple adjusted R 2 =0.18, p<0.004). Osteocalcin serum levels in children with a low ultrasound result were higher than in children with normal values (mean ± SEM: 78.2 ng/ml ± 2.9 vs 68.2 ng/ml ± 2.8, p<0.04). Tandem mass spectroscopy failed to determine traces of heparin in newborn blood. Conclusions: Children born from mothers with autoimmune diseases are at risk to develop reduced bone mass, however this effect seems to decrease with growing age. The administration of LMWH and of prednisone seem to be safe with regard to children's bone health. Disclosure of Interest: None Declared